Efeitos das variáveis ambientais locais sobre a abundância, a riqueza e a biomassa da macrofauna de solo em um ecossistema semiárido no Estado do Rio Grande do Norte, Nordeste do Brasil - Oliveira, Daniel de (2013)
The soil macrofauna is influenced to several biotic and abiotic environmental factors, from changes in the physical environment to a variety of interactions among the species involved, affecting the patterns of biodiversity of soil fauna. The power and specificity of the mechanisms that act on soil organisms vary greatly depending on environmental conditions at different scales of space and time. The Caatinga has great spatial heterogeneity of vegetation, climate and soil, so the soil macrofauna would follow this local spatial variation in the environment? This study aimed to investigate the effects of local environmental variables on biological parameters (taxa richness, total abundance and biomass) of soil macrofauna in a fragment of caatinga in João Câmara, Rio Grande Norte, Northeast Brazil. The study was conducted in the Cauaçu farm, where a grid of 2000m x 500m was drawn, and later, 30 sampling points were randomly selected. The methodology used to collect the macrofauna was the TSBF method. We tested the effects of 10 environmental variables on macrofauna across the plots and across the layers of soil. The hypothesis that macrofauna soil responds to changes in the environment was not supported throughout the plots, but was confirmed to soil layers. The soil macrofauna shows a pattern of concentration in the surface layer and decreases considerably in the deeper layers. This pattern had significant and positive relationship with the aerial plant biomass and fine root stock. The aerial plant biomass releases plant necromass that accumulates in the surface layer, providing an important source of resource and shelter for soil macrofauna, explaining their greater abundance in this layer. The roots are used as a means for the arrival of nutrients to the soil from the primary production, thus a greater amount of root conditions higher food intake for macrofauna, especially the herbivores